(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The Portrait of a Lady is the finest and perhaps, the most consummate novel of Henry James’ earlier period. It is the first novel by an American that made, within the limits of its subject, full use of the novel form. In his introduction to the novel in the New York Edition, James himself has expressed the view that he considered it the most proportioned of his productions after The Ambassadors.[1] James tells us that the starting point was the conception of a certain young woman affronting her destiny.[2] This young woman is Isabel Archer, the heroine of the novel. The action of the novel covers the growth and development of this young heroine from innocence to experience. It is her search for freedom or struggle for the affirmation and defence of her identity which constitutes the morality of the plot in the novel.